Examining asymmetric oil price exposure to assets return in Malaysia: a nonlinear ARDL approach - Chiew, Eng Woo; Sek, Siok Kun (Penerbit Universiti Kebangsaan Malaysia, 2019)
Oil is one of the most important commodities and its impact on the global economy is evident through many studies. This study is focused on examining the nine sectors of stock returns in Malaysia. The main objective is to investigate the asymmetric effects of oil price changes (oil price increases and decreases) on the sectoral stock returns in Malaysia. Besides, this study also examines the spillover effect among the sectoral stock returns in Malaysia relative to the effects of other factors. By using monthly data from 2000 to 2017, the Non-linear Autoregressive Distributed Lags (NARDL) model is applied to model the asymmetric effect of oil price changes. The study detected the asymmetric effects of oil price changes with negative effect dominant, the positive effect and oil price effect is larger in the oil intensive sectors. However, the oil price is not the main determinant factor. The main factors determining the stock returns are exchange rate, Malaysia stock market return, world stock return and sectoral spillover effect. Among these factors, the exchange rate is the main factor that influenced the stock return.